AB0906 Physical Activity in Adolescents with Juvenile Idiopathic Arthritis. (10th June 2014) - Niewerth, M.; Klotsche, J.; Foeldvari, I.; Ganser, G.; Hospach, A.; Zink, A.; Minden, K.
Abstract : Background: Physical activity (PA) is essential for the social, emotional, and cognitive development of children and adolescents. There is limited knowledge on PA in patients with juvenile idiopathic arthritis (JIA). It is of clinical relevance to what degree JIA patients are physically active despite their disease-related functional limitations. Objectives: To describe PA, to assess the relationship between PA and the burden of illness, and to analyse the trend over time regarding PA of adolescents with JIA. Methods: Cross-sectional data of adolescents with JIA recorded in the national pediatric rheumatological database in the years 2000 to 2012 were considered for the analyses. PA was defined as doing sport at least three days a week. The data of the year 2012 were used to describe the frequency and duration of PA in adolescents, its influencing factors were analysed by linear regression. Whether PA had changed between 2000 and 2012 was determined using linear mixed models by West, Welch and Galecki. Results: In 2012 a total of 2, 641 adolescents with JIA (females 64%, mean disease duration 4 years) aged 13 to 17 were recorded. About 39% of the participants were physically active (32% girls, 50% boys). Significant differences regarding the frequency of PA were observed among the various JIA categories: patients with enthesitis-related arthritis were more frequently physically active than patients with rheumatoid factor-positive polyarthritis (47% vs 29%). Regardless of the JIA subtype patients who were physically active rated their functional status, intensity of pain, and overall well-being significantly better than physically inactive patients. Multivariate analysis showed that boys, patients with a low burden of disease and patients with an inactive disease did sports more often. Considering the whole cohort, JIA patients were physically active for a median of three hours per week. During the observation period, participation in physical education at school significantly changed. In 2000 only every 4th adolescent with JIA regularly participated in physical education compared to more than 50% in 2012. Conclusions: The current recommendation [1] which advises daily PA of about 60 minutes is fulfilled only by about 40% of the adolescents with JIA. With regard to participation in physical education, a paradigm change took place, leading to fewer children extempted from school sports. References: Janssen, LeBlanc (2010). Systematic review of the health benefits of physical activity and fitness in school-aged children and youth. Int. J. Behav. Nutr. Phys. Act. 7:40 Acknowledgements: Funding: The National Pediatric Rheumatology Database has been funded by the German Children Arthritis Foundation (Deutsche Kinder-Rheumastiftung). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2562